Comparison of Diabetes Mellitus Risk Factors in Mexico in 2003 and 2014 - López Sánchez, Guillermo F.; López-Bueno, Rubén; Villaseñor-Mora, Carlos; Pardhan, Shahina (Frontiers in Nutrition, 2022)
Objective The prevalence of diabetes mellitus in Mexico is very high. This study aimed to compare the risk factors of diabetes mellitus in Mexican adults in 2003 and in 2014. Methods This study had a repeated cross-sectional design. Data from the World Health Organization (WHO) Study on global AGEing and adult health (SAGE) from Mexico (Wave 0, 2003, and Wave 2, 2014) were compared. Self-reported diabetes mellitus (outcome) was evaluated with the yes/no question: “Have you ever been diagnosed with diabetes mellitus (high blood sugar)?” Bivariate analyses and multivariable logistic regression analyses adjusted for potential risk factors were conducted. Results In 11 years (2003–2014), the prevalence of self-reported diabetes mellitus in Mexican adults increased by 2.6 times in those younger than 50 years (2003: 2.1%; 2014: 5.5%) and by 1.9 times in those ≥50 years (2003: 12.7%; 2014: 24.2%). In 2003, the risk factors associated with diabetes mellitus were female sex (OR 1.344, 95% CI 1.176–1.536), age ≥50 years (OR 6.734, 95% CI 5.843–7.760), being overweight (OR 1.359, 95% CI 1.175–1.571), obesity (OR 1.871, 95% CI 1.583–2.211), and lower physical activity of <600 MET-minutes/week (OR 1.349, 95% CI 1.117–1.630). In 2014, the exposure characteristics significantly associated with diabetes mellitus were female sex (OR 1.244, 95% CI 1.025–1.511), older age ≥50 years (OR 4.608, 95% CI 3.260–6.515), being overweight (OR 1.649, 95% CI 1.305–2.083), obesity (OR 1.778, 95% CI 1.398–2.261), and in those who had not attended/completed primary school (OR 1.360, 95% CI 1.042–1.773). Conclusion The prevalence of diabetes mellitus in Mexico significantly increased from 2003 to 2014. Female sex, age older than 50 years, and being overweight or obese were significant risk factors in both 2003 and 2014. Not having completed primary school was a new significant risk factor in 2014. Public health policies and strategies should prioritize decreasing the high levels of overweight and obesity, and improve health literacy in Mexico.